Dynamics of defensive response mobilization to approaching external versus interoceptive threat - Krause, Elischa; Benke, Christoph; Koenig, Julian; Thayer, Julian F.; Hamm, Alfons O.; Pané-Farré, Christiane A. (Biological psychiatry. Cognitive neuroscience and neuroimaging, 2018)
Background - Excessive fear and anxiety are core features of anxiety disorders. Defensive response mobilization varies dynamically with threat proximity. - Methods - We analyzed defensive responses in 48 healthy students to an approaching external, predator-like threat (an electric shock resembling a predator attack) versus an approaching threat from inside the body (feeling of dyspnea as evoked by forced breath-holding). Threats either were inevitable or could be avoided by button press. - Results - Autonomic changes (heart rate, skin conductance), defensive reflex priming (startle eyeblink response), respiratory responses, and event-related potentials were assessed. Regardless of its source, when an approaching threat was inevitable, a defensive pattern emerged characterized by an increase in skin conductance, a potentiation of the startle reflex, and bradycardia. Minute ventilation increased only with approaching dyspnea. In preparation for active avoidance of either threat, startle magnitudes were inhibited and probe-elicited P3 wave amplitudes were reduced. Moreover, generation of avoidant action resulted in heart rate acceleration. - Conclusions - This study demonstrates common and specific defensive activation patterns for approaching external and respiratory threats. The specific modulation in respiration in response to an inevitable respiratory threat may have important implications for our understanding of the etiology of anxiety disorders, especially panic disorder.